Serum vitamin D level variation in SIRS, sepsis and septic shock - BİLGİLİ, BELİZ; GÜL, FETHİ; ARSLANTAŞ, MUSTAFA KEMAL; KARAKURT, SAİT (MARMARA UNIV, FAC MEDICINE, 2019)
Objectives: Vitamin D has potent immunomodulatory effects with the capability of acting as an autocrine and paracrine agent, and inhibits inflammatory signaling. In this study, our aim was to evaluate the relationship between vitamin D levels in systemic inflammatory response syndrome (SIRS), sepsis and, septic shock patients and outcomes. Patients and Methods: A total of 45 patients whose vitamin D levels were measured within the first 48 hours of Intensive Care Unit (ICU) admission and 20 healthy controls were studied prospectively. The patients were grouped as, SIRS (Group-I,n=10), sepsis (Group-II, n=25), septic shock (Group-III, n -10) and healthy subjects (Group-IV, n=20). Serum vitamin D levels were categorized as a deficiency (<= 15ng/mL), insufficiency (16-29ng/mL) and sufficiency (>= 30ng/mL). Demographic characteristics, Acute Physiology and Chronic Health Assessment II (APACHE-II) scores, and biochemical parameters were noted. Results: Vitamin D levels were significantly lower in all study groups compared to the control group (p<0.01), but were similar among the study groups. The hospital and ICU length of stay (LOS), and biochemical parameters were similar among the study groups. The mortality rates were 40% in Group I, 57 % in Group II, and 80 % in Group III. Conclusion: In our study patients with SIRS, sepsis and septic shock had lower serum 25-OH vitamin D levels compared to the control group. Our results are in line with the literature that supports a relationship between vitamin D deficiency and inflammation.
Keywords: Critically ill patients; Vitamin D; Sepsis; SIRS; D DEFICIENCY; MORTALITY RISK; DEFINITIONS; SCORE